Bezpieczeństwo, rywalizacja, wyjątkowość. Uprawianie brazylijskiego jiu-jitsu przez mieszkańców Warszawy (studium przypadku) - Karol Górski (Etnografia Polska, 2022)
The article discusses the results of the ethnographic research conducted from 2016 to 2019 in a Brazilian jiu-jitsu club in Warsaw. I establish the conclusion that practicing Brazilian jiu-jitsu among people from the club is connected with the control over health and professional career, and is a foundation of their positive image. People from club set martial art a specific “place” in their lives. During the conducted in-depth interviews, my interlocutors rhetorically created the exceptionality of that martial art and so the exceptionality of those who trained it.